The Influence of Organizational Activities, Learning Motivation, and Family Environment on the Learning Achievement of Vocational College Students in Batam City - Pahlevi, Reza (Journal of Collaborative Industrial Management (JCIM), 2025)
Student activeness in organizations aims to develop and apply the experience gained in life. The individual's internal strength is to provide enthusiasm for learning activities. The family environment includes all interactions, emotional support, and dynamics between family members that affect child development. This study uses quantitative analysis methods. This study aimed to determine the effect of organizational activities, learning motivation, and family environment on the learning achievement of vocational college students in Batam City. From the test results obtained a significance level of 0.000 <0.05, then H4 is accepted, it can be concluded that simultaneously the variables of organizational activities (X1), learning motivation (X2), and family environment (X3) have a simultaneous effect on the learning achievement of vocational college students in Batam City.